“ADORN THE CROSS WITH ROSES”? JUSTICE AND HUMAN DIGNITY, BEAUTY AND HUMAN FLOURISHING - N. Marais (Acta Theologica)
What does beauty have to do with justice, justification, and salvation? Can the world be saved by beauty? In this contribution, some theological and rhetorical convergences and differences between the discourse on human dignity and the discourse on human flourishing are explored. The role of beauty, in these discourses, is a pivotal concern – especially as often justice and human rights shape the theological discourse on human dignity. A key proposed argument in this analysis is that justice is to human dignity what beauty is to human flourishing, and that these shape or mould the theological language with which salvation – the good news of the gospel – is articulated. The argument concludes by proposing that both forensic language and aesthetic language are born from the fold of Christian soteriology, and that not only the more static, forensic language of human dignity is required to speak about salvation, but also the more pliable, artistic language of human dignity.